Development of operational strategies of energy storage system using classification of customer load profiles under time-of-use tariffs in South Korea - Jeong, Hyun Cheol; Jung, Jaesung; Kang, Byung O. (Energies, 2020)
This study proposes a methodology to develop adaptive operational strategies of customer-installed Energy Storage Systems (ESS) based on the classification of customer load profiles. In addition, this study proposes a methodology to characterize and classify customer load profiles based on newly proposed Time-of-Use (TOU) indices. The TOU indices effectively distribute daily customer load profiles on multi-dimensional domains, indicating customer energy consumption patterns under the TOU tariff. The K-means and Self-Organizing Map (SOM) sophisticated clustering methods were applied for classification. Furthermore, this study demonstrates peak shaving and arbitrage operations of ESS with current supporting polices in South Korea. Actual load profiles accumulated from customers under the TOU rate were used to validate the proposed methodologies. The simulation results show that the TOU index-based clustering effectively classifies load patterns into 'M-shaped' and 'square wave-shaped' load patterns. In addition, the feasibility analysis results suggest different ESS operational strategies for different load patterns: The 'M-shaped' pattern fixes a 2-cycle operation per day due to battery life, while the 'square wave-shaped' pattern maximizes its operational cycle (a 3-cycle operation during the winter) for the highest profits.
Keywords: Arbitrage operation; Customer load clustering; Energy storage systems; Peak shaving; Smart grid; Time of use (TOU) tariffs; Arbitrage operation; Customer load clustering; Energy management in smart grid; Energy storage system (ESS); Peak shaving operation; Time-of-use (TOU) tariff